KATASTROFE : REINTERPRETASI SOSOK DEWI SRI SEBAGAI GAGASAN PENCIPTAAN KARYA LUKIS - Wicitra, Kirana Kusuma; Setiadi, Gabriel Aries; Nagara, Martien Roos (Jurusan Seni Rupa ISBI Bandung, 2023)
Looking back at the history meaning of Dewi Sri’s existence for Indonesian people is not only stored in her rice plant breeding tradition (seren taun) and her figure which is seen as a mere goddess of rice and plants. However, it is also related to how values, social issues and local wisdom are passed down from generation to generation. This is also illustrated through the author’s analysis and observation of the story of Wawacan Sulanjana and Dewi Sri’s role in it. Talking about values, problems and views on life that are derived is so crucial, especially when it has a significant and long-lasting effect. Art in this case exists as a medium for communicating the views and ideas of one of life’s issues, as well as re-elevating Indonesian folklore which is projected through a contemporary lens. The author uses the reinterpretation method through the author’s point of view and experience and divides it into three phases, each of which represents a different conflict. Created through the medium of oil painting. With the production of this report, it can help readers learn and provide new experiences related to the field of fine arts. Keywords: Catastrophe, Goddess Sri, Reinterpretation, Art Painting ———————————————————————————— Menelisik kembali pada sejarah makna eksistensi Dewi Sri bagi masyarakat Indonesia tidak hanya tersimpan pada tradisi pemuliaan tanaman padinya (seren taun) serta sosoknya yang dipandang sebagai dewi padi dan tumbuhan semata. Namun juga, memiliki keterkaitan terhadap bagaimana nilai- nilai, masalah sosial serta kearifan lokal diturun temurunkan. Hal ini pun tergambar melalui analisis serta observasi penulis terhadap kisah Wawacan Sulanjana dan peran Dewi Sri didalamnya. Berbicara mengenai nilai, problem serta pandangan hidup yang diturunkan ini menjadi begitu krusial terutama ketika hal itu memberikan efek yang cukup signifikan dan berkepanjangan. Seni dalam hal ini hadir sebagai media berkomunikasi terhadap pandangan dan gagasan salah satu isu kehidupan, serta sebagai pengangkatan kembali cerita rakyat Indonesia yang diproyeksikan dalam kacamata masa kini. Penulis menggunakan metode reinterpretasi melalui sudut pandang serta pengalaman penulis dan membaginya menjadi tiga fase yang masing-masing mewakili konflik yang berbeda. Diciptakan melalui medium lukis cat minyak. Dengan terbuatnya laporan ini, dapat membantu pembaca mempelajari serta memberikan pengalaman yang baru terkait bidang kesenirupaan. Kata Kunci: Katastrofe, Dewi Sri, Reinterpretasi, Karya Lukis